Computational investigation on CSF flow analysis in the third ventricle and aqueduct of sylvius - Hadzri, Edi Azali; Abdul Ghani, Ahmad Lufti; Shamsuddin, Amir Hamzah; Osman, Kahar; Abdul Kadir, Mohammed Rafiq; Abd. Aziz, Azian (IIUM Press, 2011)
In this study, a three dimensional (3D) model of the third ventricle and aqueduct of Sylvius derived from MRI scans was constructed by using Computational Fluid Dynamics (CFD) modeling. Cerebrospinal fluid(CSF) can be modeled as a Newtonian Fluid and its flow through the region of interest (ROI) was visualized using Engineering Fluid Dynamics (EFD).The constructed ROI was regarded as rigid walled and only steady state flow was able to be defined due to the limitations of current software. Different flow rate was simulated at the Foramen of Monro and a small stenosis was modeled at the middle of the aqueduct of Sylvius at a fixed location. This was made corresponding to normal patients with variation of CSF flow rate physiologically and abnormal patients with tumor causing obstruction to or within the aqueduct of Sylvius, respectively. Due to the small dimensions of the ROI geometry, gravity and complex external gravity that acted upon it was considered to be neglected. The results show as the flow rate increase, the pressure drop of CSF in the ROI proportionally increased. For normal CSF flow rate, the presence of stenosis in the aqueduct demonstrates a significant increased pressure drop.